Urgensi Waqaf dan Ibtida’ Terhadap Ketepatan Makna dalam Ilmu Tajwid Al-Qur’an - Syifa Anisa Nasution; Halimatus Sa’diah Nasution; Rabiya Al Adawia; Arjonah Syahwirada Rambe; Muhammad Kahfiki Marulafau; Muhammad Syahputra; Randy Putra Alamsyah; Mardhiah Abbas (STAI AL-AMIN, 2026)
This study examines the importance of waqf and ibtida’ in maintaining the accuracy of the meanings of Qur'anic verses. Mistakes in pausing or beginning the recitation can lead to shifts in meaning that affect the reader's understanding. Through a literature study approach, this research explores the definitions, legal basis, and classifications of waqf and ibtida’ according to classical and contemporary qira’ah scholars. Data was obtained from tajwid books, qira’ah literature, and relevant academic references. The results show that proper application of waqf and ibtida’ not only helps improve the quality of tilawah, but also preserves the continuity of the verses’ meanings so they are not interrupted or misinterpreted. Correct understanding of waqf signs in the mushaf also aids the qari in determining reading pauses. Therefore, mastery of the knowledge of waqf and ibtida’ is an essential part of performing the Qur'an recitation in a tartil manner, with precise meaning, and in accordance with the guidance of scholars.